Influence of substituent position and cavity size of the regioisomers of monocarboxymethyl-α-, β-, and γ-cyclodextrins on the apparent stability constants of their complexes with both enantiomers of Tröger's base - Řezanka, Pavel; Řezanková, Klára; Sedláčková, Helena; Mašek, Jindřich; Rokosová, Lenka; Bláhová, Markéta; Řezanka, Michal; Jindřich, Jindřich; Sýkora, David; Král, Vladimír (Journal of separation science, 2016)
Enantiomers of Tröger's base were separated by capillary electrophoresis using 2(I) -O-, 3(I) -O-, and 6(I) -O-carboxymethyl-α-, β-, and γ-cyclodextrin and native α-, β-, and γ-cyclodextrin as chiral additives at 0-12 mmol/L for β-cyclodextrin and its derivatives and 0-50 mmol/L for α- and γ-cyclodextrins and their derivatives in a background electrolyte composed of sodium phosphate buffer at 20 mmol/L concentration and pH 2.5. Apparent stability constants of all cyclodextrin-Tröger's base complexes were calculated based on capillary electrophoresis data. The obtained results showed that the position of the carboxymethyl group as well as the cavity size of the individual cyclodextrin significantly influences the apparent stability constants of cyclodextrin-Tröger's base complexes.
Keywords: Stability constants; Capillary electrophoresis; Regioisomers; Chiral separation; Cyclodextrin